2014
DOI: 10.1177/0049475513519625
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of patients admitted to the emergency department due to tick bite

Abstract: Crimean-Congo haemorrhagic fever (CCHF) is a tick-borne disease endemic in Turkey since 2002. Çorum is one of the leading five cities in Turkey in which CCHF disease is seen most. We studied characteristics of the patients with tick bites in our emergency department (ED) and determined the fatality rate of the disease in city of Çorum for the first time. We retrospectively analysed the characteristics of the patients admitted to our ED from the medical files of 21,680 patients in a 5-year period. The number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 6 publications
1
8
0
1
Order By: Relevance
“…In non-CCHF cases, these proportions were 86.4% (19), 77.3% (17) and 27.3% (6), respectively. In CCHF cases, a history of tick bite in the last 15 days was significantly higher than non-CCHF cases (p<0.05).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…In non-CCHF cases, these proportions were 86.4% (19), 77.3% (17) and 27.3% (6), respectively. In CCHF cases, a history of tick bite in the last 15 days was significantly higher than non-CCHF cases (p<0.05).…”
Section: Resultsmentioning
confidence: 93%
“…Despite these limitations, all patients admitted to our hospital were included the study. There are a few studies evaluating cases with a preliminary diagnosis of CCHF [19][20][21][22] . In this regard, there is a need for more comprehensive research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Çorum ilinde kene enfestasyonu vakalarının yaygın olduğu ve her yıl il genelinde çok sayıda Kırım-Kongo Kanamalı Ateşi (KKKA) vakasının görüldüğü bildirilmektedir (21,22). Ülkemizde her yıl binlerce kene enfestasyonu vakası olmasına rağmen insanlarda KKKA dışında diğer kene kaynaklı hastalıkların varlığına dair çalışmaların azlığı oldukça dikkat çekmektedir.…”
Section: Rickettsialesunclassified
“…Sometimes infestation is symptomless. Families can seldom see foreign bodies, which might be the cause for hospital admissions ( Erenler et al., 2014 ). A literature review reported some of the patients having dizziness, tinnitus, earache, bleeding, hearing loss, and facial paresis.…”
Section: Localization Symptoms and Signs In The Earmentioning
confidence: 99%